2012 16th IEEE Mediterranean Electrotechnical Conference 2012
DOI: 10.1109/melcon.2012.6196477
|View full text |Cite
|
Sign up to set email alerts
|

Feature extraction on vineyard by Gustafson Kessel FCM and K-means

Abstract: Image segmentation is a process by which an image is partitioned into regions with similar features. Many approaches have been proposed for color images segmentation, but Fuzzy CMeans has been widely used, because it has a good performance in a wide class of images. However, it is not adequate for noisy images and it takes longer runtimes, as compared to other method like K-means. For this reason, several methods have been proposed to improve these weaknesses. Methods like Fuzzy C-Means with Gustafson-Kessel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…23 Blackmore et al 69 argue that the 95% is the lowest barrier for the detection rate in order for the spraying process to be economically feasible. Correa et al 70 reported a 95% hit rate for red grape clusters but with artificial white background. Future work should incorporate into the developed system automatic algorithms and human-robot collaboration to improve detection performance.…”
Section: Discussion: Generalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Blackmore et al 69 argue that the 95% is the lowest barrier for the detection rate in order for the spraying process to be economically feasible. Correa et al 70 reported a 95% hit rate for red grape clusters but with artificial white background. Future work should incorporate into the developed system automatic algorithms and human-robot collaboration to improve detection performance.…”
Section: Discussion: Generalizationmentioning
confidence: 99%
“…argue that the 95% is the lowest barrier for the detection rate in order for the spraying process to be economically feasible. Correa et al . reported a 95% hit rate for red grape clusters but with artificial white background.…”
Section: Discussion: Generalizationmentioning
confidence: 99%
“…Examples include the use of an adaptive boosting (AdaBoost) classification framework, accuracy = 0.966 (Luo et al, 2016), and the implementation of the Mahalanobis distance clustering algorithm, accuracy = 0.980 (Diago et al, 2012). An alternative classification approach is an unsupervised classification, which completely forgoes manual training (Correa et al, 2012). For example, k-means clustering (KMC) (Arthur & Vassilvitskii, 2007) is a popular unsupervised technique that computes the average squared distance between pixels to determine suitable clusters.…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficiency of the process depends also on the reactors (crystallizers) design and manufacturing. Many problems are associated with this issue as described in (Barrett et al, 2005;Correa et al, 2012). The designing stage should be supported with modeling of the crystallization phenomenon.…”
Section: Introductionmentioning
confidence: 99%